Multiparametric Magnetic Resonance Imaging of Recurrent Prostate Cancer. Issue 3 (June 2016) - Mertan, Francesca V.; Greer, Matthew D.; Borofsky, Sam; Kabakus, Ismail M.; Merino, Maria.J.; Wood, Bradford J.; Pinto, Peter A.; Choyke, Peter L.; Turkbey, Baris
Abstract : Abstract: There is growing consensus that multiparametric magnetic resonance imaging (mpMRI) is an effective modality in the detection of locally recurrent prostate cancer after prostatectomy and radiation therapy. The emergence of magnetic resonance (MR)-guided focal therapies, such as cryoablation, high-intensity focused ultrasound, and laser ablation, have made the use of mpMRI even more important, as the normal anatomy is inevitably altered and the detection of recurrence is made more difficult. The aim of this article is to review the utility of mpMRI in detecting recurrent prostate cancer in patients following radical prostatectomy, radiation therapy, and focal therapy and to discuss expected post-treatment mpMRI findings, the varied appearance of recurrent tumors, and their mimics.